The pharmacotherapeutic management of duodenal and gastric ulcers. (2nd January 2022) - Mousavi, Taraneh; Nikfar, Shekoufeh; Abdollahi, Mohammad
ABSTRACT: Introduction: Although the incidence and prevalence of duodenal and gastric ulcers have been declining, it remains challenging for health care systems. Based on the underlying cause, history, and characteristics of ulcers, management is generally provided by administering proton pump inhibitors (PPIs) or antibiotics. Areas covered: This article is based on global guidelines and English language literature from the past decade obtained through searches using PubMed, Clinicaltrials.gov, the US FDA, and the Cochrane library. Using a stepwise approach, dose and duration of treatment, drug interactions, warnings and contraindications, adverse effects, and administration points were specified. New drug candidates that may get American and European approvals were also introduced. Expert opinion: Despite the wide use of PPIs, their development lags behind the clinical need. There is an absolute requirement to develop third-generation PPIs with higher potency and improved pharmacokinetic and safety profiles. Regarding the antibiotic resistance crisis, including those used against H. pylori, conducting more clinical trials and investigating regional antibiotic resistance are warranted. Potassium competitive acid blockers, ilaprazole, and an H. pylori vaccine all show promise for the future.